Uncooperative Contemporaries : Art Exhibitions in Shanghai in 2000 - Ai Weiwei; Hou Hanru; Jane DeBevoise; Lee Weng Choy; Mia Yu; Modern perspectives on art and politics in Shanghai in 2000 Here, contributions by Jane DeBevoise, Lee Weng Choy, Mia Yu, Hou Hanru, Wu Hung and Ai Weiwei, among others, analyze art in Shanghai in 2000, when artist-led initiatives and the state-led Shanghai Biennale complicated conceptions of nationalism and globalism; Wu Hung; Afterall Books London (Koln; Walther Konig, 2020)
Series Editors: Lauren Cornell, Tom Eccles, Charles Esche, Pablo Lafuente, Lucy Steeds, John Tain. Modern perspectives on art and politics in Shanghai in 2000. Shanghai's 'exhibition frenzy' in 2000 presented conflicting positions at a transitional moment for 'global' contemporary art. This book explores what was at stake for modernity, contemporaneity, nationalism, internationalism and globalism in the city at the time, while looking back from diverse perspectives today. Landmark artist-led initiatives are analysed alongside the state-led Shanghai Biennale, then in its third edition, with the terrain further complicated by public interventions and commercial initiatives. What contrasting modes of public address were developed? How did visitors engage at the time, and how may we engage afresh now? And how might this moment in Shanghai index wider transformations of the art field? With essays by Jane DeBevoise, Lee Weng Choy, Liu Ding and Carol Yinghua Lu and Mia Yu; archival texts by Xu Hong and Zhou Zixi; reflections by Ai Weiwei, Chen Lingyang, Chen Yanyin, Feng Boyi, Hou Hanru, Li Liang, Li Xiangyang, Li Xu, Liang Shaoji, Xu Zhen, Yang Zhenzhong, Yang Zhichao, Zhang Qing, Zheng Shengtian and Zhu Yu (assembled by Anthony Yung); and an introduction by John Tain.
English
Keywords: 21st century; Contemporary Art; N5300-7418 Visual Arts- History; China